The Ziswaf fund as a potential capital source for educational development in Malaysia / Azizah Daut ...[et al.] - Daut, Azizah; Che Yaacob, Ahmad; Mohd Don, Mohd Ali; Ismail, Normah; Mohamed, Safiah (2013)
Purpose - This is a concept paper that explores the prospect of establishing a model for the zakah, waqf, and infaq (ZISWAF) fund as a potential capital source for educational development in Malaysia.